2014
DOI: 10.1159/000362905
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sodium Transporters Are Increased in Urinary Exosomes of Cyclosporine-Treated Kidney Transplant Patients

Abstract: Background/Aims: Cyclosporine (CsA) is a calcineurin inhibitor widely used as an immunosuppressant in organ transplantation. Previous studies demonstrated the relationship between CsA and renal sodium transporters such as the Na-K-2Cl cotransporter in the loop of Henle (NKCC2). Experimental models of CsA-induced hypertension have shown an increase in renal NKCC2. Methods: Using immunoblotting of urinary exosomes, we investigated in CsA-treated kidney transplant patients (n = 39) the excretion of NKCC2 and Na-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Recent studies have confirmed that urinary exosomal content is altered by RAAS activation [71]. The levels of exosomal sodium transporters including sodium chloride cotransporter, alpha- and gamma-epithelial sodium channels were strongly correlated with the progression of hypertension [7175]. The miRNome analysis of urinary exosomes from hypertensive patients also proved that several miRNAs like miR-615, miR-211 were sensitive to fluctuation of blood pressure [76].…”
Section: Role Of Exosomes In Vascular Diseasementioning
confidence: 99%
“…Recent studies have confirmed that urinary exosomal content is altered by RAAS activation [71]. The levels of exosomal sodium transporters including sodium chloride cotransporter, alpha- and gamma-epithelial sodium channels were strongly correlated with the progression of hypertension [7175]. The miRNome analysis of urinary exosomes from hypertensive patients also proved that several miRNAs like miR-615, miR-211 were sensitive to fluctuation of blood pressure [76].…”
Section: Role Of Exosomes In Vascular Diseasementioning
confidence: 99%
“…Anyway, in transplanted patients, uEVs may represent a potential source for markers of drug toxicity. For example, a significant increase of NKCC2 and Na-Cl co-transporter was found in uEVs from cyclosporine-treated kidney transplanted patients compared with the controls (Esteva-Font et al, 2014). …”
Section: Evs As Renal Disease Biomarkersmentioning
confidence: 99%
“…Esteva-Font et al . found a positive correlation between plasma CsA levels and NCC abundance in uEVs of CsA-treated kidney transplant recipients [37]. Rojas-Vega et al .…”
Section: Introductionmentioning
confidence: 99%